2019
DOI: 10.1016/j.jmps.2019.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry considerations for topology design in the elastic inverse homogenization problem

Abstract: An analysis of the symmetries characterizing the micro-architecture topologies and the elastic material properties is performed. The goal is to elucidate a systematic procedure that facilitates the design of elastic metamaterial with a prescribed target elasticity tensor via inverse homogenization methodologies. This systematic procedure, which is defined through a set of rules, is based on the relationship established between the elasticity tensor symmetries and the symmetry displayed by the micro-architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 45 publications
1
31
0
1
Order By: Relevance
“…In view of these observations and following similar arguments to the ones given by [13], here, we propose to employ concepts taken from crystallography to define the cell shape. These concepts are intimately related to the symmetry properties of the crystal structures and the elastic target tensors.…”
Section: Microarchitecture Design Using Symmetric Topologiesmentioning
confidence: 83%
See 2 more Smart Citations
“…In view of these observations and following similar arguments to the ones given by [13], here, we propose to employ concepts taken from crystallography to define the cell shape. These concepts are intimately related to the symmetry properties of the crystal structures and the elastic target tensors.…”
Section: Microarchitecture Design Using Symmetric Topologiesmentioning
confidence: 83%
“…Furthermore, It has been shown that the realization of certain classes of composites, such as the Vigdergauz microstructures or the microstructures proposed by [10], could be promoted by enforcing some kind of material layout symmetry. These issues have been particularly studied in the 2D elastic material design context by the authors in previous contributions, see [3] and [13].…”
Section: Microarchitecture Design Using Symmetric Topologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wang et al (2019) showed that near-optimal and periodic truss lattice structures could be obtained for multiple load cases by distorting simple Bravais-like lattice structures to a parallelepiped. Besides using a parallelogram in 2D or a parallelepiped in 3D, one can use many more different types of polygons to solve the homogenization equations (Barbarosie et al 2017;Podestá et al 2019). For example, in 2D, a hexagon can be used to describe a periodic isotropic hexagonal microstructure (Sigmund 2000).…”
Section: Unrestricted Unit-cell Designmentioning
confidence: 99%
“…Recently in ref. [69], such kind of 2D cell derived from the hexagonal crystal system and Bravais lattices of periodic pattern were adopted. This method was extended to 3D structures—see ref.…”
Section: Cells Of Periodicity Corresponding To Exact Isotropic and Sqmentioning
confidence: 99%